Caracterização molecular e expressão de aminopeptidase (APNs) de Ostrinia nubilalis HÜBER 1796 (Lepidoptera: Crambidae) - Silva, Najara da [UNESP] (2013)
Aminopeptidases N (APNs) are a class of ectoenzymes present in the midgut of lepidopteran larvae, which participates in setting the mode of action of Bacillus thuringiensis toxin (Bt). In this work, two aminopeptidases (OnAPN5 and OnAPN6) were cloned from cells of the intestine Ostrinia nubilalis, Lepidoptera pests of temperate maize. The two sequences were identified as APNs for the presence of motifs HEXXH18 (X) and E GAMEM as well as the signal peptide. The same when analyzed correctly grouped with other aminopeptidase sequences in a tree fenogenética, can check in real time the expression in different tissues (gut, adipose tissue and carcass) from APN5 and APN6 and also a third aminopeptidase analyzed in this step APN7 work, where APN7 showed expression of 7.5 times the carcass when compared with the intestine and 4.9 times in adipose tissue when compared with the intestine while APN5 and APN6 relevant only showed expression in tissue of the intestine. These IDs APNs will facilitate studies to characterize binding interactions with Bt toxins, providing a way to understand and prevent the development of resistance to Cry proteins of B. thuringiensis. This information is fundamental to the development of appropriate strategies for managing pest resistance and its effective control